Growing Uncertainty in Marriage Expectations among U.S. Youth - Joanna R. Pepin; Philip N. Cohen (Socius, 2024)
Marriage rates are falling in the United States. The authors ask whether today’s young adults are likely to continue this trend. Using Monitoring the Future Public-Use Cross-Sectional Datasets (1976–2022), this visualization presents U.S. 12th graders’ marriage expectations. It shows declining optimism that they will be “very good” spouses and declining expectations that they will eventually marry. Both trends are prominent in the last 10 years of the survey, and both are more dramatic among young women than among young men. If these trends hold, it may foretell further declines in marriage rates in the coming years.